What Difference Does a Railroad Make? Transportation and Settlement in the BAM Region in Historical Perspective - Povoroznyuk, Olga; Schweitzer, Peter (Routledge, 2023)
Soviet and post-Soviet Siberian worlds combine physical and social remoteness with phases of accelerated industrialization campaigns. One such region is the one traversed by the Baikal-Amur Mainline (BAM) and located in mountainous landscapes underlain by permafrost. In pre-Soviet and early Soviet times, what is known as the BAM region today was more or less exclusively the domain of semi-nomadic Evenki reindeer herders and rarely traversed by Russian or other European travelers. The decision to build a railroad line through this region during the 1970s and 1980s could not but have tremendous social, demographic and ecological impacts. The specific impacts of the BAM cannot be understood, however, without considering the political and economic environments in which construction took place. In other words, the how of building the BAM was decisive in changing the ways of life, settlement, mobility, and migration patterns of indigenous residents and newcomers to the region. In the same way, the dramatic transformations of post-Soviet times need to be taken into account in order to understand the situation in the 21 st century. The article is based on on archival materials and interviews collected during multiple fieldwork visits to the region during the 2010s with a focus on the city of Tynda, the “capital” of the BAM, and indigenous village(s) Pervomaiskoe (and Chapo-Ologo) connected to the railroad. Its aim is to provide tentative answers to the title question and to explore the opportunities and constraints, or “affordances”, of infrastructure as an agent of social change.